NURSING STUDENTS’ MOTIVATION IN ONLINE ENGLISH LEARNING DURING COVID-19 PANDEMIC - Santa Maya Pramusita; Komilie Situmorang; Dwi Yulianto Nugroho (ETERNAL (English Teaching Journal), 2022)
COVID-19 pandemic has presented an enormous challenge to Indonesian education system, that is a sudden shift to online learning for all levels of education. This unplanned change may bring an impact on students’ learning motivation, either positively or negatively. A study examining students' learning motivation while studying from home, hence, is needed. This research was conducted to find out the motivation of nursing students of one private university in Tangerang in English online learning during COVID-19 pandemic. The sample was taken using a convenience sampling technique and the data were collected using a likert-scale questionnaire. The results of this study showed that nursing students’ intrinsic motivation was on moderate level with the mean score of 3.49, while their extrinsic motivation was considered high with the mean score of 3.84. Thus, the nursing students at one private university in Tangerang had higher extrinsic motivation than intrinsic motivation. This study also figured out students’ moderate level of amotivation with the mean score of 3.57. It indicated that there were several elements causing students to be demotivated in learning. These results are expected to provide an overview of nursing students’ motivation and to serve as an evaluation for enhancing the quality of future learning.